The Buddhist world - Bancroft, Anne; Harrison, Peter (Hodder Wayland London, 2001)
The teachings of the Buddha are both profoundly simple and richly complex. This book explains the beliefs common to Buddhists everywhere, and explores the variety of ways in which these are practised and describes the place of festivals, pilgrimage and mediation in the life of the believer.